Assessing the formation of cobalt carbide and its catalytic performance under realistic reaction conditions and tuning product selectivity in a cobalt-based FTS reaction. Issue 12 (3rd June 2019) - Lin, Qiang; Liu, Bing; Jiang, Feng; Fang, Xuejin; Xu, Yuebing; Liu, Xiaohao
Abstract : The formation of cobalt carbide (Co2 C) and its catalytic behavior were systematically investigated using realistic reaction conditions. Abstract : Cobalt carbide (Co2 C) has recently attracted many researchers because of arguments about properties and formation conditions. The work reported in this paper was aimed at elucidating its formation conditions and impact on catalytic activity and product selectivity by testing 20cobalt/silicon dioxide (20Co/SiO2 ) and 20cobalt/5manganese/silicon dioxide (20Co5Mn/SiO2 ) in a fixed-bed reactor under widely varied reaction conditions [230–300 °C, hydrogen/carbon monoxide (H2 /CO) = 0.5–3.0]. The results indicated that Co2 C cannot be formed at an H2 /CO of 2 because of the lower carbon diffusion rate compared to that of iron. However, a low H2 /CO of 0.5 led to Co2 C formation but required a high reaction temperature greater than 280 °C. It was interesting that Mn acting as promoter to facilitate CO dissociation clearly suppressed the formation of Co2 C as 20Co/SiO2 exhibited a higher Co2 C content, which might be because of the strong interaction between Co and Mn. A rational experimental design demonstrated that Co2 C obviously enhanced the selectivities in methane, carbon dioxide, and isohydrocarbons with a lower catalytic activity compared to metallic Co over 20Co/SiO2 under the same reaction conditions (240 °C, H2 /CO = 0.5). Also, it was found that Mn played a crucial role in regulating product distribution. At H2 /CO = 0.5 and 230–260 °C, 20Co/SiO2 showed the conventional shifting of product distribution where lighter hydrocarbons increased with reaction temperature. In contrast, 20Co5Mn/SiO2 reversed the trend as lighter C2 –C4 hydrocarbons gradually decreased with higher temperature because the surface was richer in active C* species to incorporate into growing short alkyl-Co chains, which was favorable for maximizing the middle distillate fraction. As a result, high selectivities to C8 –C16 (69.2%) and C5 –C11 (77.9%) were obtained over 20Co5Mn/SiO2 at 240 °C and 260 °C, respectively.